ANALISIS ISU GENDER: POTRET PATRIARKI DALAM FILM YUNI (2021) - Dhoni Cahyono Agung Nugroho; Martha Putri R; Rahmi Aulia Purwanti (Sintesa, 2026)
The film Yuni (2021) directed by Kamila Andini represents the social realities of young Indonesian women living under the pressures of patriarchal culture. It addresses gender issues such as child marriage, limited access to education, control over women's bodies, and the silencing of women's voices in social spaces. This study aims to analyze the representation of gender issues in the film Yuni using the Muted Group Theory perspective. The research method employs a qualitative approach with film text analysis as primary data and literature review as secondary data. The analysis results show that Yuni depicts women as a subordinate group whose voices are often ignored and must conform to the norms and language of the dominant group. The film contributes to building public awarenessregarding gender inequality and the importance of providing space for women to voice their life choices.Beyond mere reflection, Yuni functions as a strategic intervention transforming muted groups into representational counterpublics, compelling audience critical reflection on collective complicity in patriarchy reproduction. This research contributes theoretically to MGT applications in Indonesian feminist cinema and practically to anti-child marriage advocacy and gender education equityKeywords: Gender Issues; Yuni Film; Gender Representation; Muted Group Theory